PENGEMBANGAN UMKM ANDALIMAN DALAM MENDUKUNG EKONOMI KREATIF DI DESA BORBOR - Khairuddin Ependi Tambunan; Jensita Pasaribu; Melani Putri D Siregar; Marturia Lumban Gaol; Sri Ratna Hastuti Sitanggang (PT. Tangrasula Tekno Kreatif, 2026)
His study aims to examine the development of Micro, Small, and Medium Enterprises (MSMEs) based on andaliman in supporting the creative economy in Borbor Village, Borbor District. The shift toward a creativity-driven economy highlights the importance of innovation and local resource utilization at the village level. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that andaliman-based MSMEs in Borbor Village have considerable potential for further development. However, several challenges remain, including limited product innovation, reliance on traditional marketing methods, and low utilization of digital technology. Therefore, efforts to develop MSMEs through creative economy approaches such as enhancing product innovation and adopting effective marketing strategies are essential to increase product value and improve community welfare.